The Effect of Banana Stems (Musa Paradisiaca L.) Toward The Growth of Rice Field Eels (Monopterus Albus) in Cultivation Business - Hasani, Nadaul; Bahri, Syamsul; Raksun, Ahmad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Banana plants have not been utilized optimally. Banana stems can be used as a growth medium for eels. Eels are a type of freshwater animal that has quite high economic value. This research aims to determine the effect of banana stems (Musa paradisiaca L.) on the growth of rice field eels (Monopterus albus). This type of research is quantitative research with experimental methods. The research was conducted on Jl. Biduri Senteluk, Senteluk Village, Batulayar District, West Lombok Regency, NTB in the yard of the house for 3 months. The research design used was a Completely Randomized Design (CRD) with 7 treatments and 3 repetitions. Treatment P0 (100% mud) as control, P1 (90% rice field mud + 10% banana stems), P2 (80% rice field mud + 20% banana stems), P3 (70% rice field mud + 30% banana stems), P4 (60% rice field mud + 40% banana stems), P5 (50% rice field mud + 50% banana stems), and P6 (40% rice field mud + 60% banana stems). The parameters observed were absolute weight, absolute length, and survival rate of rice field eels. The research data were analyzed using the ANOVA test and the BNT test (smallest significant difference). The results of the analysis showed that the addition of banana stems had a significant effect on the growth of rice field eels (P>0.05). The best addition of banana stems was in the P3 treatment, which can be seen from the average value of the weight growth of paddy eels which increased by 6,100 grams and the increase in length growth of paddy eels by 7,200 cm, and the survival rate of paddy eels was 100%.